Sporting activity among dental students-a survey - P, VIGNESH; GANAPATHY, DHANRAJ; MP, BRUNDHA (The journal of contemporary issues in business and government, 2021)
A Dentist plays a crucial role in providing health education (General and Oral) to the community. Questions arise regarding their own health, which successively affects their patients’ counselling for leading a healthy and a physically active life. Physical activity or exercise can improve your health and reduce the danger of developing several diseases. Itcan have immediate and long-term health benefits. Most over, regular activity can improve your quality of life. The current study aimed to study the practice of physical activity among Dental students. The aim of the survey study is to create awareness and knowledge among people about Sporting activity among dental students. A questionnaire about Sporting activities among dental students, the data are collected using google forms and the results were analysed through SPSS software. Descriptive statistical analysis was carried out and chi square test was used and p value was calculated. According to the data collected about 51% of them said that 1 hour of physical activity is needed. and 37% of them said 2 hours is needed and the remaining 12% of them said 1 hour is needed. About 65% of the people have normal BMI 18.5 to 24.9, 13% of them are underweight which is less than 18.5, 10% of them are overweight 25 to 29.9 and 12% of them are obese which is 30 or more. A gender comparison was done on awareness of practicing sports on a daily basis, improvement in work life and negative effects. It was found that there was statistically non significant difference(p-value >0.05) between the awareness among the males and females in this study. Knowledge and awareness were created among dental students about sporting activities.The prevalence of physical activity was high among dental health professionals in this study. This higher prevalence of physical activity in the study group may be because the respondents were all health professionals and their income, education, and occupation likely led them to engage in healthier behaviors.